Cold hardiness of Phauda flammans (Lepidoptera: Zygaenidae) larvae - Zheng, Xia-Lin; Liu, Jun-Yan; Huang, Zong-You; Meng, Ling-Yu; Li, Jun; Lu, Wen (Entomologica Fennica, 2017)
This study aimed to determine the cold hardiness of Phauda flammans (Lepidoptera: Zygaenidae) larvae. Supercooling points of the 1st–6th instar larvae of P. flammans ranged from –7.7 to –13.0 °C. The lethal temperatures were –8 °C for 1st, –5 °C for 2nd, and –7 °C for 3rd–6th instars. Lethal times at the instar-specific lethal temperatures were 12 h for 1st, 14 h for 2nd, 15 h for 3rd, 17 h for 4th, and 18 h for 5th–6th instars. The times required for all larvae to die in an incubator at 5 °C were 30 d for 1st, 3rd, 4th, and 5th instars, and 25 d for 2nd and 6th instars. The findings suggest that P. flammans is a chill-intolerant species, and larvae will die if the air temperature decreases to –5 to –8 °C for 12–18 h or to 5 °C for 25–30 d. Such conditions are, however, unlikely to occur in southern China.